PUBLIC SPEAKING UNTUK SISWA SMK CENDEKIA KOLABORASI ANTARA FH UNIPMA DAN NEUST PHILIPPINES - Sulistya Eviningrum; Nizam Zakka Arrizal; Siska Diana Sari; Bintang Ulya Kharisma; Indriyana Dwi Mustikarini (Universitas Merdeka Madiun, 2025)
public speaking is an important communication skill in conveying messages, ideas or information orally in front of an audience. FH UNIPMA collaborates with Neust Philippines. Providing socialization on public speaking with the target being students and Cendikia High School students. The activities were divided into three sessions, namely providing material, and practicing public speaking and asking questions.The problems faced by Cendikia High School students related to public speaking are: (1) Lack of ability to appear and speak in public; and (2) Lack of public speaking skills both face to face and online.The solutions offered to solve this problem are through community service activities, namely providing training/workshops to provide tips and tricks regarding: (1) How to have the ability to appear and speak in public; and (2) Skills in public speaking both face to face and online. Implementation of this community service activity consists of 3 stages, namely; (1) Preparation stage, to identify problems, apply for permits from Cendikia High School, and make preparations for implementing public speaking training; (2) Stage of implementing public speaking training; and (3) Evaluation stage, with questions and answers as well as evaluation with the participants, to find out how much the participants' knowledge, abilities and skills regarding public speaking have increased after participating in the training activities. As a result of this activity, the audience was able to overcome nervousness and improve their ability to speak in public with more confidence and structure.